Assessment of the Quality and Shelf-Life in Enriched n3 PUFA Raw Beef Patties Using Dry Soybean Sprouts as Antioxidant - Romero, Mara Cristina (2014)
The appearance of fresh meat is a major determinant of its appeal to consumers. Ground beef in retail display oxidizes at a faster rate than whole muscle products; the use of antioxidants to break the radical chain reaction in the oxidation process is an effective method for slowing oxidation. Soybean is a complex matrix with several bioactive compounds, including peptides and proteins, isoflavones, saponins, and other compounds with antioxidant properties. This study was conducted for 1) to evaluate the antioxidant properties of dry soybeans sprouts (DSS) from Glycine max (L.) Merr., MUNASQA®; 2) to evaluate quality characteristics of raw beef patties added with dried soybean sprouts at different levels (0.5%, 1% and 2%) and soybean oil as replacer of fat; and 3) to estimate color changes and lipid oxidation of n3 fortified raw beef under frozen storage. Results showed that dry soybean sprouts had a high level of superoxide dismutase enzyme, high total phenolics and flavonoids content and appreciable vitamin c content. Although reduction power was low, 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2?-azino-bis(3-ethylbenzthiazoline-6- sulphonic acid) (ABTS) radicals scavenging activity were elevated. When different concentrations of DSS were incorporated to enriched beef patties with soybean oil, the nutritional value was slightly affected, while that n3 and n6 fatty acid content were increased around three twice. The beef patties formulated with 1% of natural antioxidant showed significantly (p < 0.05) better color stability than those without antioxidants. The lipid oxidation was inhibited in all cases, and was strongly effective at 1% concentration of DSS being the reduced percent of thiobarbituric acid reactive substances (TBARS) comparable to butilated hydroxianisole (BHA). The results shown in this research suggest that dry soybeans sprouts could also be used as a cheap natural antioxidant source for meat products.